Management Accounting - John Burns (2013)
Overview of the BookThe textbook comprises six sections which together represent a comprehensive insight into management accounting - its technical attributes, changeable wider context, and the multiple roles of management accountants. The sections cover: (1) an introduction to management accounting, (2) how organizations account for their costs, (3) the importance of tools and techniques which assist organizational planning and control, (4) the various dimensions of making business decisions, (5) the complex issues surrounding measurement of organizational performance, and (6) accounting for an organization's strategic aims and future. Spread across these sections, there are twenty-two chapters (...)